The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.48550/arxiv.2012.02435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymptotic Dimension of Minor-Closed Families and Assouad-Nagata Dimension of Surfaces

Abstract: The asymptotic dimension is an invariant of metric spaces introduced by Gromov in the context of geometric group theory. In this paper, we study the asymptotic dimension of metric spaces generated by graphs and their shortest path metric and show their applications to some continuous spaces. The asymptotic dimension of such graph metrics can be seen as a large scale generalisation of weak diameter network decomposition which has been extensively studied in computer science.We prove that every proper minor-clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Krauthgamer and Lee [16] showed that graphs of polynomial growth γ(r) ≤ Cr k embed in this sense in R O(k log k) . Bonamy et al deduce from this in [4] that graphs of polynomial growth ≤ Cr k have asymptotic dimension bounded by O(k log k). It is further shown that graphs of superpolynomial growth can have infinite asymptotic dimension.…”
Section: Definition We Define the Growth Function Of A Graphmentioning
confidence: 93%
See 2 more Smart Citations
“…Krauthgamer and Lee [16] showed that graphs of polynomial growth γ(r) ≤ Cr k embed in this sense in R O(k log k) . Bonamy et al deduce from this in [4] that graphs of polynomial growth ≤ Cr k have asymptotic dimension bounded by O(k log k). It is further shown that graphs of superpolynomial growth can have infinite asymptotic dimension.…”
Section: Definition We Define the Growth Function Of A Graphmentioning
confidence: 93%
“…Asymptotic dimension is relevant in several contexts: in geometric group theory, as groups of finite asymptotic dimension satisfy the Novikov conjecture [21], in geometry [17], [7] and in graph theory [22], [11], [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof of Theorem 1.4. It has been proved that every planar graph has asymptotic dimension at most 2 [8,23]. Thus it only remains to show that asdimpGq " 1 implies that G is quasi-isometric to a tree when G is a planar triangulation.…”
Section: The Asymptotic Dimension Of Planar Triangulationsmentioning
confidence: 99%
“…Then either asdimpGq " 2, or G is quasi-isometric to a tree (in which case asdimpGq " 1). This uses a recent result that every planar graph has asymptotic dimension at most 2 [8,23]. Theorem 1.4 cannot be extended to planar graphs with arbitrarily long facial cycles as shown by [12,Example 2.4.].…”
Section: Introductionmentioning
confidence: 99%